1995
DOI: 10.1111/j.1365-2125.1995.tb04444.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reboxetine and desipramine on the kinetics of the pupillary light reflex.

Abstract: Reflex responses were evoked by 12 light stimuli (5.3 x 10-5-3.5 mW cm-2; 500 ms), and the kinetic parameters of each response were recorded. 4 The amplitude and 75% recovery time were positively, and latency was negatively correlated with the logarithm of light stimulus intensity. In the presence of the antidepressants the latency was prolonged, the amplitude was reduced and the 75% recovery time was shortened. There was a positive linear relationship between reflex amplitude and recovery time under all three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 5 publications
4
26
1
Order By: Relevance
“…The predicted effect of desipramine on resting Table 1 pupil size would be mydriasis, reflecting mainly noradrenaline reuptake. In the present experiment, a single dose (100 mg) of desipramine failed to have a significant effect on pupil diameter, consistent with a previous observation in our laboratory (Theofilopoulos et al 1995). It should be noted, however, that in some other studies a mydriatic effect of desipramine could be observed (Szabadi et al 1980Shur and Checkley 1982;Kerr and Szabadi 1985).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The predicted effect of desipramine on resting Table 1 pupil size would be mydriasis, reflecting mainly noradrenaline reuptake. In the present experiment, a single dose (100 mg) of desipramine failed to have a significant effect on pupil diameter, consistent with a previous observation in our laboratory (Theofilopoulos et al 1995). It should be noted, however, that in some other studies a mydriatic effect of desipramine could be observed (Szabadi et al 1980Shur and Checkley 1982;Kerr and Szabadi 1985).…”
Section: Discussionsupporting
confidence: 90%
“…The shortening of the recovery time could have been secondary to the reduction in the amplitude of the reflex response, since it is well documented that smaller light reflex responses take a shorter time to recover (Smith 1988;Theofilopoulos et al 1995). However, it is unlikely that the reduction in amplitude can fully explain the shortening of the recovery time in the present experiment, since the statistical analysis of the relationship between amplitude and recovery time showed that the two doses of venlafaxine shortened the recovery time over and above that predicted on the basis of a reduction in amplitude alone.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In agreement with numerous previous reports (Flett et al 1992;Leung et al 1992;Theofilopoulos et al 1995;Bitsios et al 1996Bitsios et al , 1999bPrettyman et al 1997), there was a nearlinear positive relationship between the logarithm of intensity of the light stimulus and the amplitude of the response (Fig. 7).…”
Section: Effects Of Diazepam On Pupillary Reflexessupporting
confidence: 92%
“…In the present study, reboxetine reduced the HF power of RRI and there was an apparent trend towards decreased salivary flow, both measures usually being associated with parasympathetic regulation. These results are consistent with previous notions of diminished salivation (Szabadi et al 1998) and changes in the pupillary light reflex (Theofilopoulos et al 1995), and seem to imply that reboxetine, despite its low affinity for muscarinic receptors in vitro (Riva et al 1989), may produce measurable anticholinergic activity in vivo. The reduced salivation has been proposed to be due to the blockade of noradrenaline uptake at the synapse of the preganglionic salivary neurone, which could potentiate the inhibition of the parasympathetic salivary output (Szabadi et al 1998).…”
Section: Reboxetinesupporting
confidence: 92%